2017
DOI: 10.7717/peerj.4181
|View full text |Cite
|
Sign up to set email alerts
|

Examining the stress-burnout relationship: the mediating role of negative thoughts

Abstract: BackgroundUsing Smith’s (1986) cognitive-affective model of athletic burnout as a guiding framework, the purpose of this study was to examine the relationships among athletes’ stress in life, negative thoughts, and the mediating role of negative thoughts on the stress-burnout relationship.MethodsA total of 300 college student-athletes (males = 174; females = 126, Mage = 20.43 y, SD = 1.68) completed the College Student Athlete’s Life Stress Scale (CSALSS; Lu et al., 2012), the Automatic Thoughts Questionnaire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 53 publications
0
13
0
2
Order By: Relevance
“…Previous studies have suggested that cAMP levels increase in butyrate-containing cell cultures or in the intestinal epithelial cells of butyrate-fed mouse ( Ghanim et al., 2009 ). Therefore, intestinal epithelial cells can use butyrate as a key energy substrate to produce ATP ( Chang et al., 2017 ). At the same time, patients with colitis benefit from butyrate enema, indicating its local anti-inflammatory effects ( Guo et al., 2015 ; Chu et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that cAMP levels increase in butyrate-containing cell cultures or in the intestinal epithelial cells of butyrate-fed mouse ( Ghanim et al., 2009 ). Therefore, intestinal epithelial cells can use butyrate as a key energy substrate to produce ATP ( Chang et al., 2017 ). At the same time, patients with colitis benefit from butyrate enema, indicating its local anti-inflammatory effects ( Guo et al., 2015 ; Chu et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…He also highlighted that coping skills directed at modifying those cognitions may help reduce burnout (Smith, 1986). The importance of a cognitive component in mediating the stressburnout relationship has been confirmed in recent studies (Chang et al, 2017;Moen et al, 2019). Gustafsson et al's (2011) integrated model for athlete burnout incorporates aspects of Smith's model while also identifying several factors that increase the athlete's vulnerability to stress, thereby elevating their risk for burnout.…”
Section: Perfectionistic Cognitions and Burnoutmentioning
confidence: 99%
“…Kondisi ini disebut sebagai burnout. (39,40) Kondisi ini selanjutnya akan mempengaruhi kualitas hidup. (41,42) Pada penelitian ini, dilakukan pengolahan data dengan program SPSS menggunakan uji Chi-square untuk menentukan hubungan antara stres akademis dan kualitas hidup pada remaja.…”
Section: Pembahasanunclassified